Linking Space Observations with Ground Surveys to Better Understand Wisconsin’s Conservation Agricultural Landscape - Herro, Alana (Proceedings of the Wisconsin Space Conference, 2020)
Cover cropping and no-till or minimum tillage are conservation farming techniques that have numerous benefits for the environment but are not always adopted by farmers because of risks of reduced yield and/or reduced profits. Precise and accurate methods of tracking conservation farming would improve the ability of researchers to maximize benefits and minimize risks. In this paper, satellite data is processed using an expert classification intended to identify cover crops in Wisconsin from the years 2009/2010 to 2018/2019. The results of a survey about farmers’ experiences with conservation farming practices is also summarized. The locations of cover cropped farms, identified in the survey, are used to assess the accuracy of the 2018/2019 map produced using the expert classification. The map was found to have an accuracy of only 51%. The survey results found that cover crops and no-till or minimum tillage did not tend to negatively affect yields or profits.